THE INFLUENCE OF WRITING PROCESS METHOD AND MOTIVATION TOWARD THE TENTH GRADE STUDENTS’ WRITING ABILITY OF DESCRIPTIVE TEXT AT SMA NAHDATUL ULAMA PALEMBANG - Rika Novi Yarti (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThe study deals with the influences of Writing Process Method, Conventional Teaching Technique, and Motivation towards students’ writing ability to the tenth grade students of SMA Nahdatul Ulama Palembang. This is a quantitative study. The data were collected by using questionnaire, pre-test and post-test. They were analyzed by using t-test and Two Way Anova. Findings show that there were significant influence of Writing Process Method, Conventional Teaching Technique and Writing Motivation to the tenth grade students’ writing ability. There were interaction effect from the Writing Process Method and Writing Motivation to the tenth grade students. There was a significant influence in writing ability between the tenth grade students who had high learning motivation and those who had low learning motivation taught by using Writing Process Method. In, conclusion Writing Process Method and Writing Motivation show significant roles to improve the tenth grade students’ writingability in descriptive text.Keywords : Writing Process Method, Conventional Teaching Technique, Motivation, Writing ability.